2000
DOI: 10.1139/f99-232
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the effects of site exposure, plant growth form, water depth, and transparency on aquatic plant biomass

Abstract: The maximum depth of macrophyte colonization and depth distribution of macrophyte biomass were assessed over 3 years, in late summer, at six sites in the St. Lawrence River and two sites in the Ottawa River (Lake des Deux Montagnes). Maximum depth of submerged plant colonization could be predicted from the light extinction coefficient (r2 = 0.82) and Secchi disk depth (r2 = 0.80). The aboveground and total biomass of macrophytes were related to a variety of environmental variables as follows in descending orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Aquatic plants grown in slow flows and/ or shallow water generally possess less flexible, but stronger stems than those inhabiting fast running water or deep waters (Brewer & Parker, 1990;Usherwood et al, 1997;Bociag et al, 2009;Miler et al, 2010Miler et al, , 2012. Additionally, the canopy-forming species generally have much higher growth rate than species with other growth forms in lakes with low-light availability (Keddy, 1983;Chambers & Prepas, 1988;Hudon et al, 2000). Therefore, these results can finally suggest that C. demersum was the most adaptive species to both deep water and rapid floods.…”
Section: Mechanical Resistance Response To Water Depth and Flood Intementioning
confidence: 92%
See 1 more Smart Citation
“…Aquatic plants grown in slow flows and/ or shallow water generally possess less flexible, but stronger stems than those inhabiting fast running water or deep waters (Brewer & Parker, 1990;Usherwood et al, 1997;Bociag et al, 2009;Miler et al, 2010Miler et al, , 2012. Additionally, the canopy-forming species generally have much higher growth rate than species with other growth forms in lakes with low-light availability (Keddy, 1983;Chambers & Prepas, 1988;Hudon et al, 2000). Therefore, these results can finally suggest that C. demersum was the most adaptive species to both deep water and rapid floods.…”
Section: Mechanical Resistance Response To Water Depth and Flood Intementioning
confidence: 92%
“…Light availability significantly affects the maximum biomass and colonization depth of SAV (Keddy, 1983;Chambers & Prepas, 1988), as well as the mechanical resistance of terrestrial plants . Hydraulic forces from waves and winds can significantly affect the mechanical resistance of SAV, resulting in mechanical damages (e.g., stem breakage, uprooting, or other damages) (Koehl, 1984;Schutten et al, 2005), which ultimately have adverse effects on plant growth (Idestam-Almquist & Kautsky, 1995;Hudon et al, 2000). Stem mechanical properties and root anchorage strength are the essential traits of mechanical resistance for the reduction of these mechanical damages in aquatic habitats (Handley & Davy, 2002;Schutten et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…This estimation was deemed conservative since both the biomass (Lévesque et al 2017) and maximum depth of colonization (i.e. water transparency, see Hudon et al 2000) of submerged aquatic vegetation are lower in Lake Saint-Pierre than for fluvial lakes located upstream.…”
Section: Contribution Of Primary Producers To Carbon Fixation and Nutmentioning
confidence: 99%
“…Hudon et al (2000) found the biomass and distribution of submerged macrophytes to be influenced by site exposure and differences in species distribution attributable to growth form. Sand-Jensen (1989) held decrease in water depth responsible for increase in the wave-induced turbulent forces on the bottom.…”
Section: Exposure To Wind and Wavesmentioning
confidence: 99%